Emissão de gases de efeito estufa da mudança de uso do solo e potencial de sequestro de C-CO2 pela recuperação de pastagens degradadas para o estado do Pará, 2008 a 2019 - Santos, Gustavo Goes dos (Universidade Federal de São Carlos, 2021)
Brazil actively contributes to the intensification of the global greenhouse effect, with deforestation being responsible for a large part of the country's atmospheric carbon emissions. It is necessary to conserve the Amazon biome from an environmental and economic point of view since the biome's ecosystem services are resources for farming. This work aims to estimate the greenhouse gas (GHG) emissions due to the cutting and burning of native forests in the period 2008 to 2019, to evaluate, in the same time frame, the potential variations of the soil organic carbon (SOC) stocks for the state of Pará, and to propose strategies to increase SOC stock in the recovery of degraded pastures. The deforestation calculation pointed to 3.53 Mha of forest cover loss in the state of Pará between 2008 and 2019, equivalent to 2.8% of the total area of the state. The change in land use culminated in an emission of 1025.52 Mton. CO2eq. in the state of Pará, while the conversion of land suitable for farming into pasture without tillage and with low input of organic amendments, using standardized methodological values, showed potential to increase the SOC stock by 45.93 Mton. C year-1 in the first 30 centimeters of soil in the state. It was found that most municipalities in Pará increased their pasture areas between 2008 and 2019, with emphasis on the five municipalities with the greatest advance in pasture in the period (São Félix do Xingu, Altamira, Novo Repartimento, Novo Progresso and Pacajá), also responsible for the highest rates of deforestation and CO2eq. emissions in the state of Pará. The GHG mitigation projections were divided according to the degree of implementation of the crop-livestock-forest integration system (ILPF) in a total area of degraded pastures, based on regional agricultural suitability. In scenario A, which computes the introduction of 20 to 40% of the ILPF system in the total degraded pastures of the state of Pará, a mitigation potential of 8.90 to 17.81 Mton. CO2eq. year-1 is estimated, while scenario B – between 60 and 100% conversion of degraded pastures in the state of Pará into ILPF system – represents a GHG mitigation potential between 26.71 and 44.51 Mton. CO2eq. year-1 . It can be concluded that there was a correlation between deforestation, GHG emissions and the advancement of pastures in the state of Pará between 2008 and 2019, as well as the degradation rates per municipality can help in the establishment of public policies and takeover decision-making by the private sector.
Greenhouse gas emissions from land use change and potencial sink of C-CO2 by recovery of degraded pastures for the state of Pará, 2008 to 2019
Keywords: Desmatamento; Mudança climática; Sistema integrado; Estoque de carbono; Sustentabilidade; Deforestation; Climate change; Integrated system; Carbon stock; Sustainability; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA